The Analysis of Main Characters in Michel Gondry’S Movie Eternal Sunshine of Spotless Mind ( 2004 ): Sigmund Freud’s Psychoanalysis Approach - Mardasari Mardasari; M Amir P.; Harlina Sahib (Hasanuddin University, 2024)
This research is entitled about analysis of main characters in Eternal sunshine of the spotless mind movie by Michel Gondry and uses Sigmund freud’s psychoanalysis approach. This research aims to analyze the personality dynamic and how they solve their problem with using the defense mechanism by Sigmund freud’s psychoanalysis in main characters. The results show that there are life instincts and death instincts (personality dynamic) that exist in the main characters. In this study, the main characters have changed in feelings that exist in him or her commonly referred to the psychoanalysis theory is the life instinct (Joy, motivating people to create and maintain new life, positive emotions such as love and affection) and the death instinct (Fear, anxiety or instincts that lead to not wants someone to live). In this movie, most of the death instincts that occur in the Joel and Clem as main characters. This movie also explains about 2 people who fall in love and have different characters and at the end of the story they want to forget all the memories in their brains and souls by using a tool called mapping (a tool that is placed in a person's head to erase the memories in their brain). The main character uses the defense mechanism of repression. In other words, repression is a defense mechanism that a person uses to forget or eliminate various thoughts that exist in their soul.